2013
DOI: 10.1158/1940-6207.capr-13-0171
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Colon and Small Intestinal Tumorigenesis in APCmin/+ Mice By SHetA2 (NSC721689) without Toxicity

Abstract: The occurrence of intestinal polyps in people at high risk for developing colorectal cancer provides an opportunity to test the efficacy of chemoprevention agents. In this situation of treating otherwise healthy people, the potential for toxicity must be minimal. The small molecule flexible heteroarotinoid (Flex-Het), called SHetA2, has chemoprevention activity in organotypic cultures in vitro and lack of toxicity at doses capable of inhibiting xenograft tumor growth in vivo. The objective of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 37 publications
(71 reference statements)
2
34
0
Order By: Relevance
“…The small molecule compound SHetA2 significantly reduced incidence and size of intestinal polyps, both in males and females. 22 In contrast, in a dietary study using the retinoidx-receptor agonist bexarotene, a greater reduction of intestinal tumors was found in male mice compared to female mice. 31 The observation that we did not find differences between genders could be attributed to the fact that we administered a flat-fixed dose to all mice, based on the bodyweight of male mice.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The small molecule compound SHetA2 significantly reduced incidence and size of intestinal polyps, both in males and females. 22 In contrast, in a dietary study using the retinoidx-receptor agonist bexarotene, a greater reduction of intestinal tumors was found in male mice compared to female mice. 31 The observation that we did not find differences between genders could be attributed to the fact that we administered a flat-fixed dose to all mice, based on the bodyweight of male mice.…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, the Apc Min/C mouse model is one of the most studied models of intestinal tumorigenesis in which tumor growth is suppressed by different anticancer agents. 22,23 In the present study we used fasting as a pre-conditioning method to protect against the side-effects of irinotecan. Previously, we reported that 3-days of fasting increases stress-resistance, including upregulation of the Nrf2 pathway, which is involved in the protection against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…5C), and pronounced suppression of the AOM/DSS-induced inflammatory enzyme cyclooxygenase 2 (COX-2; Fig. 5D), important key factors in CRC progression, was observed in response to CA supplementation (5, 43). In addition, AOM/DSS-induced oxidative damage targeting nuclear DNA was attenuated by CA supplementation as indicated by reduced staining for 8-oxodG, an effect that was observed only in the ‘CA11’ supplementation group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Published studies suggested that ginseng not only has cancer prevention potential [4,5,11,12] , but also has anti-inflammatory effects [13,14] . Various data suggest that ginseng reduces inflammation and suppresses colitis by restoring gut homeostasis [15–17] , and this anti-inflammatory activity likely plays a critical role in cancer prevention and treatment [18–20] .…”
Section: Introductionmentioning
confidence: 99%